2013
DOI: 10.3389/fncel.2013.00117
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β induces synaptic dysfunction through G protein-gated inwardly rectifying potassium channels in the fimbria-CA3 hippocampal synapse

Abstract: Last evidences suggest that, in Alzheimer's disease (AD) early stage, Amyloid-β (Aβ) peptide induces an imbalance between excitatory and inhibitory neurotransmission systems resulting in the functional impairment of neural networks. Such alterations are particularly important in the septohippocampal system where learning and memory processes take place depending on accurate oscillatory activity tuned at fimbria-CA3 synapse. Here, the acute effects of Aβ on CA3 pyramidal neurons and their synaptic activation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 79 publications
2
70
0
Order By: Relevance
“…Hippocampal slices were prepared as described previously (Nava‐Mesa et al, ). Briefly, animals were deeply anesthetized with halothane (Fluothane; AstraZeneca) as suggested by the Ethical Committee because of its high efficacy and quick action and received buprenorphine intramuscularly as analgesic (0.01 mg/kg; # 062,009, BUPRENODALE®; Albet).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal slices were prepared as described previously (Nava‐Mesa et al, ). Briefly, animals were deeply anesthetized with halothane (Fluothane; AstraZeneca) as suggested by the Ethical Committee because of its high efficacy and quick action and received buprenorphine intramuscularly as analgesic (0.01 mg/kg; # 062,009, BUPRENODALE®; Albet).…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously reported that Aβ induces a reduction in gene expression of hippocampal GirK subunits (Mayordomo‐Cava, Yajeya, Navarro‐Lopez, & Jimenez‐Diaz, ) and decreases GirK conductance inducing an increase in excitability in CA3 pyramidal neurons (Nava‐Mesa, Jimenez‐Diaz, Yajeya, & Navarro‐Lopez, ). We also found in behaving mice that GirK‐dependent signal enhancement rescued hippocampal functions in an in vivo mouse model of early Aβ pathology (Sanchez‐Rodriguez et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that hippocampal Aβ injections in rat are sufficient to induce reductions in GABAergic input to the hippocampus and to exhibit aberrant θ oscillations (Villette et al, 2010). In a separate study of the fimbria-CA3 complex postsynaptic response, Aβ also induces a significant decrease in late inhibitory postsynaptic currents (IPSCs) (Nava-Mesa et al, 2013). Treatment of somatosensory neurons with soluble Aβ as much as 1 µM has also been found to decrease agonist-evoked GABA A responses and to depress monosynaptic GABA A receptor-mediated IPSCs to 60% of control levels on average, whereas a reversed sequence control peptide is ineffective (Ulrich, 2015).…”
Section: Aβ and Synaptic Functionsmentioning
confidence: 99%
“…Further, when GABAergic pathways were stimulated, Aβ selectively antagonized the slow inhibitory postsynaptic potential mediated by GABA B receptors. This effect was linked to the GIRK component of GABA B -mediated signaling, and the authors suggested that one function of Aβ may be to decrease GIRK channel conductance (Nava-Mesa et al, 2013).…”
Section: Alzheimer's Diseasementioning
confidence: 98%
“…Amyloid-β peptide (Aβ), a key effector of Alzheimer's disease, induces aberrant patterns of neural activity, destabilizes neuronal networks, and impairs LTP formation (Huang & Mucke, 2012;Palop & Mucke, 2010;Shankar et al, 2008). Recent work has shown a link between Aβ peptides and GIRK channel function (Nava-Mesa, Jimenez-Diaz, Yajeya, & Navarro-Lopez, 2013). Specifically, the application of Aβ peptide in hippocampal slices significantly depolarized neurons and concurrently increased input resistance, suggesting that these peptides close constitutively active channels.…”
Section: Alzheimer's Diseasementioning
confidence: 99%